UPAYA MENINGKATKAN KREATIVITAS GURU DALAM MENGAJAR MELALUI METODE DEMONSTRASI DI SD NEGERI 03 BUANA BAKTI KABUPATEN SIAK - Parji (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article discusses the improvement of teachers’ teaching creativity through the application of the demonstration method. Teaching creativity plays a crucial role in enhancing the quality of students’ learning outcomes, as creativity involves the ability to design innovative learning products and activities. Pre-research observations conducted on August 2, 2022, at SD Negeri 03 Buana Bakti Siak identified several problems: (1) teaching materials were monotonous and lacked creativity, resulting in low student interest; (2) teachers had not actively involved students in the learning process, limiting the development of students’ creative thinking skills; and (3) teaching media were rarely used, making lessons less engaging. This study employed School Action Research (PTS). The results indicate that applying the demonstration method increased teachers’ teaching creativity. Teacher acceptance of the method improved, and teaching creativity aspects increased from 59.0% in Cycle I to 73.8% in Cycle II.